The application of human resource accounting systems in public shareholding companies in Jordan - Alrawashedh, Nahed Habis (International Journal of Psychosocial Rehabilitation, 2020)
The current research aimed at studying the application of human resource accounting systems in Jordanian shareholding companies by a quantitative approach. Designed questionnaire distributed on 98 financial managers of public holding companies in Jordan (listed in the Jordanian stock market); the number of the companies included in this study was 34 companies with big and medium size. The results showed that managers of the tested companies think that Jordanian companies are in need for human resources accounting system and are ready and able to apply it in their systems.